2012
DOI: 10.3758/s13420-012-0092-4
|View full text |Cite
|
Sign up to set email alerts
|

Level of deprivation does not affect degree of discounting in pigeons

Abstract: Two experiments tested the effects of food deprivation on discounting in pigeons. An adjusting-amount procedure was used to estimate the subjective value of food at delays ranging from 1 to 24 s. Experiment 1 compared pigeons’ discounting of delayed food reinforcers at 75-80% and 90-95% of free-feeding weight. Experiment 2 compared discounting under 1-hr and 23-hr food deprivation. In both experiments at both deprivation levels, discounting was well described by the hyperboloid discounting function. No systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
0
17
0
11
Order By: Relevance
“…Oliveira et al (2013) proposed that choice in nonhuman animals may well be influenced more by relative, rather than absolute, rates of reinforcement, consistent with the matching law (Herrnstein, 1970). Specifically, in the context of the effect of deprivation on discounting rate, they suggested that deprivation in animals might result in proportionally equivalent changes in the subjective value of both reinforcer alternatives.…”
Section: Generality Of Discountingmentioning
confidence: 94%
See 1 more Smart Citation
“…Oliveira et al (2013) proposed that choice in nonhuman animals may well be influenced more by relative, rather than absolute, rates of reinforcement, consistent with the matching law (Herrnstein, 1970). Specifically, in the context of the effect of deprivation on discounting rate, they suggested that deprivation in animals might result in proportionally equivalent changes in the subjective value of both reinforcer alternatives.…”
Section: Generality Of Discountingmentioning
confidence: 94%
“…Richards et al (1997) found no effect of water deprivation on rats’ discounting rates, and Ostaszewski and colleagues did not observe a consistent effect of food deprivation in rats (Ostaszewski, Karzel, & Bialaszek, 2004; Ostaszewski, Karzel, & Szafranska, 2003). Oliveira, Calvert, Green, and Myerson (2013) manipulated food deprivation in pigeons in two ways. In their first experiment, food deprivation was manipulated by varying free-feeding body weight (i.e., discounting was studied at both 75% and 95% of free-feeding body weight), and in their second experiment, food deprivation was manipulated by varying time since the last feeding (i.e., discounting was studied after both 1 and 23 hours of food deprivation).…”
Section: Generality Of Discountingmentioning
confidence: 99%
“…Research with humans also suggests that lower income levels (i.e., greater deprivation) may be associated with steeper delay discounting functions, indicating that impulsiveness might increase in conditions of economic deprivation (e.g., Green, Myerson, Lichtman, Rosen, & Fry, 1996; but see Oliveira, Calvert, Green, & Myerson, 2013). Although the evidence of the effects of deprivation on discounting in animals is mixed (e.g., Bradshaw & Szabadi, 1992;Eisenberger, Masterson, & Lowman, 1982;Oliveira et al, 2013), Laude, Pattison, and Zentall (2012) found that deprivation did affect suboptimal choice in pigeons. They presented pigeons with a choice between signalled 50% food (the suboptimal alternative) and unsignalled 75% food (the optimal alternative).…”
Section: Factors Related To Self-controlmentioning
confidence: 99%
“…In contrast, experiments with rats, pigeons, and primates all place the subjects under some level of restriction; however, the various levels are associated with varied results (for review, see Richards et al, , Experiment 2). Multiple studies have assessed the effects of manipulating restriction on the rate of discounting for food and water with rats (Ostaszewski, Karzel, & Szafranska, ; Richards et al, ) and for food with pigeons (Oliveira et al, ). All three experiments found that no matter how restriction of food or water was manipulated, there was no systematic difference on discounting.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the combination of factors such as delay and amount of the outcome, choice behavior (e.g., choosing between a smaller-sooner and larger-later reward) would appear difficult to predict. The discounting framework has allowed for the study of more complex choice behavior, like the function of delay on choice behavior (e.g., Bickel, Odum, & Madden, 1999;Calvert, Green, & Myerson, 2010;Green, Fry, & Myerson, 1994;Green, Myerson, Holt, Slevin, & Estle, 2004;Mazur, 2000;Myerson & Green, 1995;Oliveira, Calvert, Green, & Myerson, 2013).…”
mentioning
confidence: 99%